Investigation of a large gap cold plasma reactor for continuous in-package decontamination of fresh strawberries and spinach. (January 2020) - Ziuzina, D.; Misra, N.N.; Han, L.; Cullen, P.J.; Moiseev, T.; Mosnier, J.P.; Keener, K.; Gaston, E.; Vilaró, I.; Bourke, P.
Abstract: The aim of this work was to investigate the efficacy of a large gap atmospheric cold plasma (ACP) generated with an open-air high-voltage dielectric barrier discharge (DBD) pilot-scale reactor, operated in either static (batch) or continuous mode for produce decontamination and quality retention. Significant reductions in the bacterial populations inoculated on the strawberries and spinach were obtained after the static mode of ACP treatment with 2.0 and 2.2 log10 CFU/ml reductions for E. coli and 1.3 and 1.7 log10 CFU/ml reductions for L. innocua, respectively. Continuous treatment was effective against L. innocua inoculated on strawberries, with 3.8 log10 CFU/ml reductions achieved. No significant differences in colour, firmness, pH or total soluble solids (TSS) was observed between control and ACP-treated samples with the effects of treatment retained during the shelf-life period. The pilot-scale atmospheric air plasma reactor retained the strawberry quality characteristics in tandem with useful antimicrobial efficacy. Industrial relevance: This in-package plasma technology approach is a low-power, water-free, non-thermal, post-package treatment. Generating cold plasma discharges inside food packages achieved useful antimicrobial effects on fresh produce. Depending on the bacterial type, produce and mode of ACP treatment significant reductions in the populations of pathogenic microorganisms attached to the fresh produce was achieved within 2.5 min of treatment. The principal technical advantages include contaminant control, quality retention, mitigation of re-contamination and crucially the retention of bactericidal reactive gas molecules in the food package volume, which then revert back to the original gas. Highlights: A pilot-scale cold plasma system enhanced the microbiological safety of fresh strawberry and spinach. Static mode was effective for reduction of E. coli inoculated on produce. Continuous treatment reduced L. innocua by 3.8 log cycles on strawberries. Microbial inactivation was achieved in combination with produce quality retention. Plasma discharge and gas composition diagnostics revealed the principal effector chemical species generated.